2017
DOI: 10.1186/s12885-017-3670-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of programmed death ligand-1 expression in breast cancer: a meta-analysis

Abstract: BackgroundProgrammed cell death-ligand 1 (PD-L1) may be a useful molecule for targeted immunotherapy. Therefore, this meta-analysis aimed to investigate PD-L1 expression in breast cancer and its associations with clinicopathological factors and outcomes, which may help determine whether PD-L1 expression is a useful prognostic marker.MethodsThe Medline Ovid, Cochrane, PubMed, Google Scholar, and Web of Knowledge databases were searched for studies that evaluated the prognostic or clinicopathological significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Results from two meta‐analyses including partially overlapping studies confirmed the greater PD‐L1 expression in TNBC compared with non‐TN subtypes but were not consistent in reporting the association between HER2 status and PD‐L1 expression.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Results from two meta‐analyses including partially overlapping studies confirmed the greater PD‐L1 expression in TNBC compared with non‐TN subtypes but were not consistent in reporting the association between HER2 status and PD‐L1 expression.…”
Section: Methodsmentioning
confidence: 88%
“…A possible explanation for such observations may be attributable to the immune escape phenomenon. Indeed, a high expression of PD‐L1 may reflect the activation of the immune checkpoint PD1/PD‐L1 pathway leading to the mitigation of the host's antitumor immune response, thus ultimately resulting in increased tumor aggressiveness . Although intriguing, further evidence is needed in order to confirm this hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…Both findings are linked to a better clinical outcome as proven from the studies mentioned above. Many studies have been conducted in order to evaluate the prognostic value of PDL1TC, PDL1IC and TILs in IBC, and even after many meta-analyses some results remain conflicting (41,59,60). Kim et al (60), conducted an meta-analysis which included 7,877 cases and was led to the conclusion that PDL1TC expression is associated with poorer DFS.…”
Section: Figure 1 (A) Pd-l1 Expression In Tumor Cells (×20) (B) Pd-mentioning
confidence: 99%
“…The fact that cancer cells upregulate PD-L1 expression in response to virus infection is of importance as several meta-analysis studies have shown that PD-L1 expression is of prognostic value in multiple types of cancer including TNBC and could help clinicians to discriminate patients who will and will not respond to therapeutics targeting PD-1/PD-L1 interaction. [47][48][49][50] Recently there has been a growing interest in combining different types of OVs with ICIs to improve therapeutic efficacy. 41 A study published by Bourgeois-Daigneault et al tested oncolytic Maraba virus in neo-adjuvant setting in TNBC models where they found that their OV sensitized the otherwise refractory tumors to ICIs.…”
Section: Discussionmentioning
confidence: 99%